Morphologic and gene expression criteria for identifying human induced pluripotent stem cells. - Shohei Wakao; Masaaki Kitada; Yasumasa Kuroda; Fumitaka Ogura; Toru Murakami; Akira Niwa; Mari Dezawa (PLoS ONE, 2012)
Induced pluripotent stem (iPS) cells can be generated from somatic cells by the forced expression of four factors, Oct3/4, Sox2, Klf4, and c-Myc. While a great variety of colonies grow during induction, only a few of them develop into iPS cells. Researchers currently use visual observation to identify iPS cells and select colonies resembling embryonic stem (ES) cells, and there are no established objective criteria. Therefore, we exhaustively analyzed the morphology and gene expression of all the colonies generated from human fibroblasts after transfection with four retroviral vectors encoding individual factors (192 and 203 colonies in two experiments) and with a single polycistronic retroviral vector encoding all four factors (199 and 192 colonies in two experiments). Here we demonstrate that the morphologic features of emerged colonies can be categorized based on six parameters, and all generated colonies that could be passaged were classified into seven subtypes in colonies transfected with four retroviral vectors and six subtypes with a single polycistronic retroviral vector, both including iPS cell colonies. The essential qualifications for iPS cells were: cells with a single nucleolus; nucleus to nucleolus (N/Nls) ratio ∼2.19: cell size ∼43.5 µm(2): a nucleus to cytoplasm (N/C) ratio ∼0.87: cell density in a colony ∼5900 cells/mm(2): and number of cell layer single. Most importantly, gene expression analysis revealed for the first time that endogenous Sox2 and Cdx2 were expressed specifically in iPS cells, whereas Oct3/4 and Nanog, popularly used markers for identifying iPS cells, are expressed in colonies other than iPS cells, suggesting that Sox2 and Cdx2 are reliable markers for identifying iPS cells. Our findings indicate that morphologic parameters and the expression of endogenous Sox2 and Cdx2 can be used to accurately identify iPS cells.